2016
DOI: 10.1021/acs.jchemed.6b00367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Flipped, Large-Enrollment Organic Chemistry Course on Student Attitude and Achievement

Abstract: Organic Chemistry is recognized as a course that presents many difficulties and conceptual challenges for students. To combat the high failure rates and poor student attitudes associated with this challenging course, we implemented a "flipped" model for the first-semester, largeenrollment, Organic Chemistry course. In this flipped course, lectures were replaced by short videos, which were delivered via a course management system, and class time was reserved for problem solving and other active learning activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
139
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(147 citation statements)
references
References 42 publications
8
139
0
Order By: Relevance
“…Large enrolment courses are fraught with many challenges, such as lack of learner engagement and participation, lack of opportunities to attend to learner differences, excessive workload for instructors, and impersonalisation of teaching (Iipinge, 2013). Flipping has been found to demonstrate increased participation (McLaughlin et al, 2014), increased learner emotional satisfaction and intellectual accessibility when compared to traditional large lecture courses (Mooring, Mitchell, & Burrows, 2016) and improved performance and learner satisfaction (Deslauriers, Schelew, & Wieman, 2011;Eichler & Peeples, 2016;Love et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Large enrolment courses are fraught with many challenges, such as lack of learner engagement and participation, lack of opportunities to attend to learner differences, excessive workload for instructors, and impersonalisation of teaching (Iipinge, 2013). Flipping has been found to demonstrate increased participation (McLaughlin et al, 2014), increased learner emotional satisfaction and intellectual accessibility when compared to traditional large lecture courses (Mooring, Mitchell, & Burrows, 2016) and improved performance and learner satisfaction (Deslauriers, Schelew, & Wieman, 2011;Eichler & Peeples, 2016;Love et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Also in Organic Chemistry, Mooring et al (2016) studied the effect of flipping a large-enrollment university course on students' grades and attitude toward the course. They had students watch pre-class videos and answer pre-class online quizzes.…”
mentioning
confidence: 99%
“…Research findings on the impact of flipped-classes on students' attitudes have been mixed. Some research studies have found students reporting higher levels of satisfaction in flipped-classes due to more active learning activities (Foertsch, Moses, Strikwerda, & Litzkow, 2002;Lage & Platt, 2000;Mooring, Mitchell, & Burrows, 2016;Prince, 2004), feeling more engaged (Enfield, 2013;McLaughlin et al, 2014;Tune, Sturek, & Basile, 2013), and having access to videos that can be reviewed as many times as desired (Brunsell & Horejsi, 2013;Schultz, Duffield, Rasmussen, & Wageman, 2014). However, other studies have found students' levels of satisfaction is reduced in flipped-classes due to (Doyle, 2008;Strayer, 2012;Tolman & Kremling, 2017), disinclination toward the requirement of managing their own learning (Hagen & Fratta, 2014), student preference to get content from instructor and not peers (Engin, 2014), and resistance to moving away from their pre-conceived beliefs that an instructor's job is to lecture to passive students (Amresh, Carberry, & Femiani, 2013;Enfield, 2013).…”
Section: Flipped-class Design Impact On Students' Attitudes-satisfactionmentioning
confidence: 99%